Predicting progression of bladder urothelial carcinoma using microRNA expression. (6th February 2013) - Rosenberg, Eran; Baniel, Jack; Spector, Yael; Faerman, Alexander; Meiri, Eti; Aharonov, Ranit; Margel, David; Goren, Yaron; Nativ, Ofer
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Recurrence and progression prediction in urothelial cancer is currently based on clinical and pathological factors: tumour grade, tumour stage, number of lesions, tumour size, previous recurrence rate, and presence of concomitant carcinoma in situ. These factors are not specific enough to predict progression and ∼50% of patients diagnosed as high risk in fact do not progress within 3 years. Patient follow‐up is both expensive and unpleasant (frequent invasive cystoscopies). Molecular biomarkers, including microRNAs have been studied to provide additional prognostic information for these patients, but to date no molecular biomarker has become the 'gold standard' for patient diagnosis and follow‐up. We used Rosetta Genomics' highly specific microRNA expression profiling platforms to study the prognostic role of microRNAs in bladder cancer. Using microdissection we chose specific tumour microRNAs to study in order to avoid background contamination. Tumour progression was associated with altered levels of microRNAs. In particular, high expression levels of miR‐29c* were associated with a good prognosis. The study found that the use of microRNAs for determining progression and invasiveness for patients with urothelial cancer could potentially have a substantial impact on the treatment and follow‐up individual patients. Objective To identify microRNAs that could be useful as prognostic markers for non‐muscle‐invasive (NMI) bladder carcinoma. Patients and Methods Formalin‐fixed, paraffin‐embedded samples of 108 NMI bladder carcinomas, and 29 carcinomas invading bladder muscle were collected, and microRNA expression levels were measured using microarrays. For 19 samples, microdissection was performed to compare microRNA expression between the tumour and surrounding tissue. MicroRNAs that were found to be unrelated to the tumour itself were excluded as potential prognostic markers. Results Expression profiles identified microRNAs that were differentially expressed in NMI tumours from patients who later progressed to carcinoma invading bladder muscle compared with NMI tumours from patients that did not progress. The microRNA profile of tumours invading the bladder muscle was more similar to that of NMI tumours from patients who later progressed, than to that of the same‐stage NMI tumours from patients who did not later progress. The expression level of one microRNA, miR‐29c*, was significantly under‐expressed in tumours that progressed and could be used to stratify patients with T1 disease into risk groups. Conclusions MicroRNAs can be useful biomarkers for prognosis in patients with urothelial carcinoma. In our study, expression levels of several microRNAs, including miR‐29c* identified high‐ and low‐risk groups. These biomarkers show promise for the stratification of patients with bladder cancer.